Hubungan Pengetahuan Gizi dan Pola Konsumsi Sumber Fe dengan Kejadian Anemia Pada Santriwati di Pondok Pesantren Al-Mizan Muhammadiyah Lamongan - Dinda Ayu Lestari Basuki; Fanti Septia Nabilla; Lailatul Muniroh (Media Gizi Kesmas, 2023)
Background: Hemoglobin (Hb) is positioned lower than usual in the blood in the condition known as background anemia. Anemia can beget inadequate blood to bind and transport oxygen from the lungs throughout the body. Women suffer from anemia more frequently than men, especially pregnant women, youthful women and the poor. This is in agreement with the physiologica requirements of women who increase during  gestation and also the factor of bleeding through  period that occurs every month. Anemia can reduce individual work capacity. People who witness anemia generally frequently feel headaches and dizziness. The negative impact of anemia is that it can intrude with internal processes and reduce intelligence, bloodied impunity, and reduce the capacity to learn objectsObjectives: The purpose of this study was to dissect the relationship between nutritive knowledge and consumption patterns of iron sources with the prevalence of anemia in adolescents, especially youthful women.Methods: This research is an analytic observational study with a cross-sectional research design which was conducted on a sample of 50 female students from class X and XI at the Al-Mizan Muhammadiyah Lamongan Islamic Boarding School. Samples were selected by proportional random sampling method.Results:The outcome from the study showed that the level of nutritional knowledge of respondents is 50% in the less category. The pattern of consumption of Fe sources of respondents 64% never consumed Fe sources. There is a relationship between the level of nutritional knowledge (p=0.016) and consumption patterns of iron sources (p=0.036) with the incidence of anemia in female students. Conclusions: Teenage girls with a good level of nutritional knowledge and a level of consumption of iron sources that are in accordance with needs effect on reducing the risk of anemia. It is hoped that young women can increase their intake of foods that are sources of iron and increase their knowledge about which foods have a large amount of iron and which foods are iron inhibitors to prevent anemia.